The role of a distant typhoon in extending a high PM2.5 episode over Northeast Asia - You, Seunghee; Kang, Yoon Hee; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Atmospheric Environment, 2021)
In Northeast Asia, high-pressure systems typically initiate high PM2.5 episodes. However, the role of low-pressure systems, including typhoons, in high PM2.5 episodes is not well understood. In this study, we attempted to explain the evolution of the high PM2.5 episode event that was initiated by a migratory high-pressure system and the extension of the event in the presence of low-pressure systems. To achieve this aim, we conducted a multilateral analysis of a high PM2.5 episode that occurred in October 2015 in Northeast Asia using surface observation data, satellite measurements, weather maps, trajectory analyses, and three-dimensional air quality simulations. The analysis results revealed the discrete steps of the event. First, air pollutants over inland China were transported to Northern China by an anticyclone in the region. Then, in Northern China, elevated PM2.5 concentrations were observed in the following 2–3 days due to local emissions under the enhanced stagnant conditions in addition to the transported air pollution from inland China. Subsequently, under the influence of a slow-moving migratory high-pressure system in China, South Korea (a downwind area of China) experienced a high (>50 μg/m3) PM2.5 episode due to the transboundary transport of PM2.5 and local emissions. Usually, high PM2.5 episodes in South Korea under similar meteorological conditions last up to five days. However, during this period, the synoptic displacement of the high-/low pressure systems at 35°–38° latitudes in the region caused an extended (e.g., four or more days) of air pollutant residence time in Northeast Asia. Further, Typhoon Champi located in the northern Pacific (about 500 km south of Japan) interfered with the eastward movement of the high-pressure system located in the downwind area, which resulted in poor ventilation conditions for PM2.5 and its precursors. Thus, we determined that Typhoon Champi played a crucial role in maintaining PM2.5 concentrations over 50 μg/m3 for nine days or longer. We also noted that the aforementioned steps also occurred for another extended PM2.5 episode under the influence of a distant low-pressure system in the past. The findings of this study warrant further investigation of the relationship between extended PM2.5 episodes in Northeast Asia and distant typhoons.
Keywords: Air pollutants; High PM2.5; High pressure system; High/low-pressure system displacement; Low pressure systems; Northeast Asia; Northern China; PM$-2.5$; Regional transport; Remote typhoon; High PM2.5; High/low-pressure system displacement; Regional transport; Remote typhoon; Ventilation